Analysis of Correlation Between Diatoms in Surface Sediments and Water Quality of Reservoirs in Source Region of Le'anhe River - HU Qiannan; JI Yong; YAN Ruyu; ZHANG Yue; WANG Yipeng; JIN Yi; BAI Dongchen (Renmin Zhujiang)
To explore the trophic level and the response of diatoms in surface sediments of reservoirs in the source region of Le'anhe River to the water environment,this paper conducts research on Duanxin Reservoir,Zhanggongshan Reservoir,Zhonglyu Reservoir,Datangwu Reservoir,and Shijing Reservoir in the source region of Le'anhe River.By the trophic level index (TLI),principal component analysis,and redundancy analysis (RDA),the water quality environment and the diatoms in surface sediments are taken as the research object and the research carrier,respectively,and the trophic state of reservoirs and the relationship between diatoms in surface sediments and water quality are qualitatively analyzed.The research results reveal that ① the water quality of Duanxin Reservoir belongs to Class I,i.e.,in a mesotrophic state;the water quality of Shijing Reservoir seriously exceeds Class V,i.e.,in a mid-eutrophic state;the water quality in other reservoirs are in Class III,namely,in a mesotrophic state.② The distribution characteristics of diatom communities have a good indicator effect on the water environment of Le'anhe River.For example,genera and species such as Aulancoseiragrannulata are mainly distributed in water bodies with good water quality and at a mesotrophic level,and genera and species such as Cyclostephanos tholiformis are more indicative of water bodies with poor water quality and a high trophic level in the source region of Le'anhe River.③ RDA indicates that the three water quality factors of SD,DO,and TP can explain the variation laws of diatom assemblage to a great degree.